Elevated serum ferritin: What should GPs know? - Goot, K.; Hazeldine, S.; Bentley, P.; Olynyk, John; Crawford, D. (The Royal Australian College of General Practitioners, 2012)
Background: Elevated serum ferritin is commonly encountered in general practice. Ninety percent of elevated serum ferritin is due to noniron overload conditions, where venesection therapy is not the treatment of choice. Objective: This article aims to outline the role of the Australian Red Cross Blood Service Therapeutic Venesection program, to clarify the interpretation of the HFE gene test and iron studies, and to describe the steps in evaluating a patient with elevated serum ferritin. Discussion: After exclusion of hereditary haemochromatosis, investigation of elevated serum ferritin involves identifying alcohol consumption, metabolic syndrome, obesity, diabetes, liver disease, malignancy, infection or inflammation as causative factors. Referral to a gastroenterologist, haematologist or physician with an interest in iron overload is appropriate if serum ferritin is >1000 µg/L or if the cause of elevated serum ferritin is still unclear.